Advances in human aspects of aviation - Landry, Steven J. (Boca Raton, Fla. : CRC Press, 2013)
"Edited by two experts in this field, this book covers the design of aircrafts for the comfort and well being of the passenger. It includes strategies and guidelines for maximizing comfort, the design of aircrafts including cockpit design, and the training and work schedules for flight attendants and pilots"--
section 1. Flight deck interfaces -- section 2. Air traffic control interfaces and operations -- section 3. Human performance in aviation -- section 4. Automation and function allocation -- section 5. The next generation air transportation system (nextgen) -- section 6. Modeling -- section 7. Safety and ethics -- section 8. Cognition and workload -- section 9. Experiments and evaluation.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Aeronautics -- Human factors; Electronic books